PENGARUI.I VARIASI PENYUDUTAN ARAH SINAR PADA PE$$ERIKSAAN VERTEBRA LUMBASACRAL JOINT PROYEKSI LATERAT TERHADAP KRITERIA ANATOMI RADIOGRAF - Utami, Asih Puji (Jurnal Ilmu dan Teknologi Kesehatan, 2011)
There are variations in x-ray beam angulation applied in examining lumbosacral joint lateral projmtion, both heoretical and practical. According to Clark (1973) examination of lumbo"sacral joint laieral projecti'on'uses beam cirection of 0 ', Ballinger (1999) stated that x-ray beam is directed 5 o to 8 o caudally and Bontrager (zaOq ranging from 5 o to 10 0 to the caudally. The purpose of this study is to investigate the inflLence of x-riy beam'angiraion to :aCicgraphic anatomical criieria and to find the. most appropriate x-ray beam angulation tc achieve good radiographic anatomical criteria conducted in examining lumbosacral joint lateral projections uiing r-6y beam angulaiion of 0 n, S o, 10 o and 15 o caudally. The study was experimental with observatiorial method approach. Observation is done by examining lumbosacral joint lateral projections with the variations of x-ray beam angulations of 0 o, 5 o, 10 o and 1S " caudally. Thf Cata is collected by conducting tests, and spreading questionnaires (check tist). There are 1S observers in spreading questionnaires, Radiographic results are recorded as experimental documents. Methods of data analyiis used Cescriptive analysis by simple regression and crosstab data. Data are codified and categoriz.J in.n. The results of this research showed that there are positive significant and ionelation between x-ray beam angulation variations of 00,50, 100, 150 caudally to the radiographic-anatomical critena produced on eximining lumbosacraljoint lateral projection. lt is indicated by p vatue = o.oto (<o.os), means tta is acceiiJil f; ;;il;t"i Ihe best x-ray beam angulation is 150 caudally. This angulation can pioduce good radiographic anatomical criteria.Key words: criteria